2020
DOI: 10.2478/aiht-2020-71-3425
|View full text |Cite
|
Sign up to set email alerts
|

Redox and essential metal status in the brain of Wistar rats acutely exposed to a cadmium and lead mixture

Abstract: Most Pb and Cd neurotoxicity studies investigate exposure to either of the toxic metals alone, while data on co-exposure are scarce. The aim of our study was to fill that gap by investigating acute combined effects of Pb and Cd on redox and essential metal status in the brain of Wistar rats. Animals were randomised in four groups of six to eight rats, which received 15 or 30 mg/kg of Cd, 150 mg/kg of Pb, or 150 mg/kg of Pb + 15 mg/kg of Cd by gavage. The fifth, control, group received distilled water only. Co-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Animal studies have found oxidative damage from As, Cd, and Pb [ 31 , 32 , 33 ]. Some studies have proved the interaction between essential metals and toxic metals [ 34 , 35 ]; however, the mechanisms of multiple metal exposure are unclear. Identifying the inflammation of metal mixtures is troublesome due to the independent, antagonistic, or additive interactions between toxic metals and essential elements.…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have found oxidative damage from As, Cd, and Pb [ 31 , 32 , 33 ]. Some studies have proved the interaction between essential metals and toxic metals [ 34 , 35 ]; however, the mechanisms of multiple metal exposure are unclear. Identifying the inflammation of metal mixtures is troublesome due to the independent, antagonistic, or additive interactions between toxic metals and essential elements.…”
Section: Introductionmentioning
confidence: 99%
“…A major factor that makes the brain prone to oxidative damage is its low antioxidant system compared to other organs. The neurotoxic effect of cadmium (Cd) was shown in many studies [33][34][35][36]. Its mechanism of neurotoxicity is associated with an increase in the generation of ROS, resulting in oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols present in Trévo include pomegranate, lycopene, βcarotene, ascorbic acid, and omega-3 and omega-6 fatty acids. These antioxidant phytochemicals can prevent, delay, or reverse neurological disorders [33,[50][51][52][53][54][55][56]. They probably also contribute to the antioxidant properties of Trévo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhouab et al, [8] demonstrated that Pb, Cd, arsenic, and mercury co-exposure led to higher neurotoxic effects compared to the effects induced by co-exposure to three or fewer of the same metals. Similarly, Javorac et al, [9] reported that oxidative status induced by exposure of rats to metal mixtures was absent during treatment with the individual metals.…”
Section: Introductionmentioning
confidence: 92%